Socialization of the Utilization of Rejected Bread and Expired Milk as Maggot Feed in Palaran Sub-District - Akhmat Rizkuna; Suhardi Suhardi; Ari Wibowo; Anhar Faisal Fanani; Cori Qamara; Novemia Fatmarischa (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
This socialization activity is a community service program that is carried out to build the lives of people in Handil Bakti, Palaran District, Samarinda City, East Kalimantan. This service aims to socialize the benefits of rejected bread and expired milk as maggot feed. So that farmers are independently able to utilize bread and milk waste into animal feed which can minimize the costs incurred. Through a participatory and collaborative approach, this program was attended by 15 people who work as maggot farmers, laying hen farmers, ornamental chicken farmers, and the surrounding community. The service was carried out using lecture and discussion methods by means of delivery by resource persons and direct discussion. It is hoped that this socialization can open farmers' insights about waste that has the potential to be used as maggot feed. The results obtained during the training were the participants' understanding of the benefits of rejected bread and expired milk which can be used as a source of maggot feed.